Study of Permanent Magnet Synchronous Motor With LQG Controller and Observer On The Hydraulic Pump System - Setiawan, Paulus; Linda Meilani; Denny Dermawan; Freddy Kurniawan; Okto Dinaryanto (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2023)
In today's aircraft industry, the flight control system and landing gear system cannot be separated from the role of the hydraulic technology system. As the prime mover of the hydraulic pump or actuator hydraulic system, a permanent magnet synchronous motor (PMSM) is used. This PMSM is a substitute for the role of conventional combustion engines, and PMSM is considered to have several advantages in increasing performance and efficiency. This research will develop a system to find parameter values for Linear Quadratic Gaussian (LQG) controllers in a hydraulic pump system that is installed as a load from PMSM and then observe and analyze the performance of the response of the synchronous motor system, namely in the form of changes in rotor rotation speed, torque electric power, and stator current on the q-axis. The results of the research on the characteristics of the PMSM implemented in the hydraulic pump system show that the LQG controller is more optimal when compared to the observer controller. The LQG controller is known to have a faster transient response, which is indicated by the value of the settling time improvement at no load, namely 116.67% for the observer controller and 364.705% without the controller. Then when the synchronous motor serves the nominal load, the rotational speed of the rotor produced in the steady state becomes 8.29% faster than the observer controller and 74.49% without the controller. This rotor's rotational speed affects the time the actuator needs to extend and retract motion.